LEXICOGRAPHIC GLOSSARY OF LINGUISTIC TERMS IN ISOCHLI DICTIONARIES OF ENGLISH AND UZBEK LANGUAGES - Akbarova Gulnoza Zakirovna (American Journals, 2023)
A dictionary is a collection of terms that has been compiled and organized for a specific purpose. Lexicography (Greek lexicon - dictionary and grapho - write) is the study of the theoretical and practical concepts of lexicography. Lexicographers are professionals who create dictionaries. Lexicography's responsibilities include organizing lexicographers' work, creating card files that serve as the foundation for dictionary compilation, systematizing and maintaining them, and developing the principles and methods of dictionary compilation. In this article, thoughts and comments are made about the lexicographic analysis of linguistic terms in English and Uzbek annotated dictionaries.
Keywords: lexicography, English language, Uzbek language, dictionary, linguistics, terms, annotated dictionaries, formation, development, words, word units, semantic structure, lexicographer.